2020
DOI: 10.1681/asn.2020060829
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Receptor (SuPAR) in COVID-19–Related AKI

Abstract: BackgroundAKI commonly occurs in patients with coronavirus disease 2019 (COVID-19). Its pathogenesis is poorly understood. The urokinase receptor system is a key regulator of the intersection between inflammation, immunity, and coagulation, and soluble urokinase plasminogen activator receptor (suPAR) has been identified as an immunologic risk factor for AKI. Whether suPAR is associated with COVID-19–related AKI is unknown.MethodsIn a multinational observational study of adult patients hospitalized for COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 69 publications
6
100
1
16
Order By: Relevance
“…Soluble urokinase plasminogen activator receptor (suPAR) seems to be such a screening tool. We and others, recently demonstrated that suPAR concentrations above 6 μ g/l herald worsening to SRF 14 days earlier 4,5 . The positive predictive value for the early prediction of SRF was as high as 85.9%.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Soluble urokinase plasminogen activator receptor (suPAR) seems to be such a screening tool. We and others, recently demonstrated that suPAR concentrations above 6 μ g/l herald worsening to SRF 14 days earlier 4,5 . The positive predictive value for the early prediction of SRF was as high as 85.9%.…”
Section: Introductionmentioning
confidence: 67%
“…An important point of the SAVE study is the strategy to select for early anakinra treatment using the predictive biomarker suPAR. In previous studies in COVID-19 and in sepsis, this marker turned out to be able to predict the likelihood for unfavourable outcome 4,5,8,9 .…”
Section: Discussionmentioning
confidence: 95%
“…None of the patients with suPAR < 4.60 ng/ml required dialysis. The highest suPAR tertial was strongly associated with incident AKI (aOR: 9.15; 95%CI: 3.64−22.93) 158 . In view of these results, suPAR might be used as a potential biomarker for AKI and COVID‐19 severity.…”
Section: Complicationsmentioning
confidence: 88%
“…A pilot clinical study has also shown high levels of soluble urokinase-type plasminogen activator receptor (suPAR) in COVID-19 patients [76]. COVID-19 patients with high suPAR levels are at higher risk of developing severe respiratory failure [76] and acute kidney injury [77], which confirms the importance of fibrinolysis in the severity of the disease. There is therefore a need for research focusing on the role of fibrinolysis and its components in the pathogenesis of 10…”
Section: Accepted Manuscriptmentioning
confidence: 91%